Материалы к изучению экологии форелей рек Прикарпатья - Алтухов, Е.А.; Булатович, М.А. (Вестник зоологии, 1968)
The schools of Salmo trutta morpa fario L. and S. gairdneri irideus G i b b. inhabi-ting the north-western Carpathian rivers — Prut, Lomnitsa, Zhonka, Orava —. are characterized by the predominance of young age groups. In S. gairdneri irideus G i b b. the two-summer individuals are predominant, S. trutta-morpha fario L. is distinguished by the presence of two- and three-summer individuals and a considerable amount of immature ones. Sex ratio is not similar in different rivers. The benthic organisms — larvae of Ephemeroptera, Plecoptera, Trichoptera and Diptera are the main food for the both species. The qualitative composition of food organisms being similar, the larvae of Epheme-roptera and Plecoptera are predominant in the food of S. gairdneri irideus G i b b. and. -those of Trichoptera — in S. trutta morpa fario L.